Hemoglobin targets for chronic kidney disease patients with anemia: a systematic review and meta-analysis. - Zhou Jing; Yuan Wei-jie; Zhu Nan; Zhou Yi; Wang Ling (PLoS ONE, 2012)
Background Numerous studies have identified a relationship between hemoglobin (Hb) levels and mortality in patients with chronic kidney disease (CKD), which have raised concerns about the optimal Hb targets in correction of anemia. Our study is designed to investigate the potential effects of targeted Hb levels, aiming to give some evidence for therapy of renal anemia. Methodology/principal findings A comprehensive search of Medline, Embase and the Cochrane Database of Systematic Reviews was performed in December 2011 and updated in February 2012 for any new trials. Randomized trials designed to evaluate effects of high (generally the Hb about 13.0 g/dL) and low Hb (generally the Hb about 10.0 g/dL) targets on clinical outcomes in CKD patients with anemia were collected. All statistical analysis was calculated using the RevMan software available free from the Cochrane Collaboration. 24 trials involving 10361 patients were identified. Our findings demonstrated a statistically significant increased risk of mortality in the high Hb levels (RR 1.18; 95% CI 1.02 to 1.37) while the high and low Hb groups were both treated with ESAs. Overall, compared with low Hb levels, high Hb levels are associated with increased risk of hypertension (RR 1.40; 95% CI 1.11 to 1.75), stroke (RR 1.73; 95% CI 1.31 to 2.29), and hospitalizations (RR 1.07; 95% CI 1.01 to 1.14). However, there are no significant differences in the risk of non-fatal myocardial infarction (RR 1. 13; 95% CI 0.79 to 1.61) and renal replacement therapy (RR 1. 00; 95% CI 0.85 to 1.18). Conclusions/significances Targeting low Hb levels are beneficial to CKD patients especially in the predialysis population. The optimal Hb targets to aim for in CKD patients and at what Hb level the risks of adverse events begin to increase remain elusive. Future studies are still needed to elucidate these questions.